EMPOWERMENT OF THE CIDAHU VILLAGE COMMUNITY THROUGH RE-BRANDING OF OPAK MSMES AS OVOP PRODUCTS AND THE CREATION OF STREET GANG SIGNS IN KKN-T ACTIVITIES OF GUNUNG JATI INDEPENDENT UNIVERSITY - Bayu Rayhan Syawaludin; Ocha Aulia Marsinda; Misbak Misbak; Maslahatul Mahmudah; Rifqi Faijar; Rijal Ardhi Purnama; Steven Julianto; Firlyana Frischa Nabilla; Dwi Setiawan Julianto; Mohammad m.indrawan6@gmail.com Indrawan; Fikri Izzan Al-Anshah; Melinda Affrina Saputri; Nur Wulan Imadri; Ageng Fitra Aidin (Jurnal Abdisci, 2026)
Background. The Thematic Real Work Lecture (KKN-T) of Universitas Swadaya Gunung Jati is an implementation of the Tri Dharma of Higher Education, which focuses on community service. This activity was conducted in Cidahu Village, Cidahu District, Kuningan Regency, in response to the need to enhance the identity of local products and improve the village environment. Methods. The main goal of the program is to empower the community through the rebranding of Opak MSMEs as a village flagship product (One Village One Product / OVOP) and the installation of street signs to improve order and accessibility of the area. Methods. The methods used include field observation, questionnaire distribution, and participatory discussion. Result. The results of the activity show that there is an improvement in the image of MSME products through the creation of logos, and new packaging designs. The installation of street alley signs facilitates the mobility of residents, provides clarity of direction, strengthens village identity, and improves traffic safety. Conclusion. In conclusion, KKN-T activities not only contribute to local economic development but also improve environmental governance based on community participation. Implication. The implication of this activity is the need for continuous support and assistance from various parties so that the benefits produced can continue to grow and have a long-term impact on the welfare of the people of Cidahu Village.